Contact-free impacts of sessile reef organisms on stony coral productivity - Engelhardt, Kara E.; Vetter, Jana; Wöhrmann-Zipf, Franziska; Dietzmann, André; Proll, Franziska M.; Reifert, Hannah; Schüll, Ilona; Stahlmann, Max; Ziegler, Maren; Justus Liebig University Giessen (My University, 2023)
Coral reefs are biodiversity and productivity hotspots where space limitation makes interactions between organisms inevitable. Biodiversity loss alters these interactions, however downstream effects on the productivity of individual species remain unexplored. Here, we quantified immediate and long-term changes in stony coral productivity in response to contact-free interactions with various benthic organisms (stony corals, soft corals, macroalgae, sponges). We show that corals sense the presence of other organisms and subsequently modulate their productivity. Each stony coral species had a characteristic reaction to contact-free stimuli, while the identity of the interaction partner was of subordinate importance. Our data highlight downstream effects that biodiversity loss and shifting coral reef communities may have through indirect modulation of productivity, resulting in uneven effects among species. The productivity response is probably mediated by secondary metabolites released into the water. The underlying communication pathways that mediate these interactions remain to be investigated.
Keywords: ddc:570